2012
DOI: 10.1007/s00428-012-1267-2
|View full text |Cite
|
Sign up to set email alerts
|

PI3KCA mutations and/or PTEN loss in Her2-positive breast carcinomas treated with trastuzumab are not related to resistance to anti-Her2 therapy

Abstract: The purpose of this study is to evaluate whether activating mutations of the p110α catalytic subunit of class A phosphoinositide 3-kinases (PI3KCA) or complete loss of phosphatase and tensin homolog (PTEN) is associated with response to anti-human epidermal growth factor receptor 2 (Her2) treatment in breast cancer (BC). We analysed PI3KCA hot-spot mutations and PTEN immunohistochemical expression in 129 Her2-positive infiltrating BC treated with trastuzumab, including 26 cases treated with neoadjuvant therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…After exclusion of duplicate references, nonrelevant literature, and those that did not satisfy the inclusion criteria, 19 candidate articles were included. AHT was used for advanced breast cancer in eight studies [13][14][15][16][17][18][19][20], in eight studies in the neoadjuvant setting [21][22][23][24][25][26][27][28], in two adjuvant trials [29,30], and in one study in both metastatic and neoadjuvant disease [31]. Tables 1, 2, 3, 4, 5 and 6 outline the main study characterizes and the outcomes of the 19 included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After exclusion of duplicate references, nonrelevant literature, and those that did not satisfy the inclusion criteria, 19 candidate articles were included. AHT was used for advanced breast cancer in eight studies [13][14][15][16][17][18][19][20], in eight studies in the neoadjuvant setting [21][22][23][24][25][26][27][28], in two adjuvant trials [29,30], and in one study in both metastatic and neoadjuvant disease [31]. Tables 1, 2, 3, 4, 5 and 6 outline the main study characterizes and the outcomes of the 19 included studies.…”
Section: Resultsmentioning
confidence: 99%
“…AHT was combined with taxenes in three studies [16,19,31], while no chemotherapy was used in two studies [14,18] and in one arm in a third study [15]. Table 2 shows that five studies reported on objective response rate (ORR) of WT versus MT subgroups [13,14,[18][19][20]31], while five studies reported survival outcomes [15-17, 19, 20]. Table 3 shows that there were 828 patients with early stage breast cancer, 671 (81 %) and 157 (19 %) patients had WT and MT PIK3CA tumors, respectively.…”
Section: Studies In Metastatic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…As trastuzumab, T-DM1 suppresses the phosphatidylinositol 3′-kinase (PI3K) signaling pathway [40]. The potential association between PIK3CA mutational status and T-DM1 efficacy remains unknown, but the results from clinical breast cancer series suggest that trastuzumab benefit does not depend on the mutational status of PIK3CA [55,56] or tumor PTEN expression [57]. …”
Section: Resistance To T-dm1mentioning
confidence: 99%
“…Potential molecular mechanisms of trastuzumab resistance in these patient groups were evaluated in several studies. Furthermore, many studies exploring potential prognostic factors to identify clinical determinants have failed to reach a definitive conclusion [10,11]. In our study, we examined prognostic factors affecting the recurrence-free survival (RFS) in patients with HER2-positive EBC treated with 52 weeks of adjuvant trastuzumab.…”
Section: Introductionmentioning
confidence: 99%